Using Second Derivative of Transient Pressure in Welltest Analysis of Low Permeability Gas Reservoirs - Bahrami, H.; Rezaee, M. Reza; Kabir, A. (SPE, 2010)
Welltest interpretation requires diagnosis of reservoir flow regimes in order to determine the basic reservoir characteristics such as average reservoir permeability and skin factor. Due to wellbore storage effect, wellbore phenomena and complexity of reservoir response from heterogeneous reservoir layers, detection of the reservoir flow regimes using standard welltest diagnostic plots might be challenging and have some uncertainties.In pressure transient testing, there are instances where the flow regimes might not clearly be revealed on diagnostic plots of pressure build-up and its derivative, such as incomplete pressure build-up tests, low permeability reservoirs and multi-phase producing wells. In such cases, the Semi-Log plot of first and second derivative of transient pressure versus time can be used to reduce the uncertainties associated with welltest analysis.This paper describes a new method for well test interpretation using second derivative of transient pressure. Two field examplesare shown in which a reliable radial flow regime on pressure build-up data could not be detected using standard plots. The second derivative approach was used to predict radial flow regime trend and estimate the reservoir permeability and skin factor, which the results were in good agreement with production data in these wells.